Pengaruh Pertumbuhan Penjualan, Ukuran Perusahaan dan Tangibility Assets Terhadap Struktur Modal - Andrayani, Ni Putu Devi; Negara Sudirman, I Made Surya (E-Jurnal Manajemen; Vol 3 No 5 (2014), 2014)
The objective of this research is to find influence signification of sales growth, firm size and tangibility of assets on capital structure in insurance company at BEI. The total of taken sample is 7 insurance companies, by busing purposive sampling method and analysis technique which is used is double linear regression analysis. Based on the analysis result, sales growth has positive influence and significant to capital structure, firm size to capital structure has negative influence and significant, asset tangibility has no effect on thecapital structure.
Keywords: Growth, Size, Tangibility, Capital Structure